An area-efficient 128-channel spike sorting processor for real-time neural recording with 0.175 μ W/channel in 65-nm CMOS - Do, Anh Tuan (2020)
This paper presents a power- and area-efficient spike sorting processor (SSP) for real-time neural recordings. The proposed SSP includes novel detection, feature extraction, and improved K-means algorithms for better clustering accuracy, online clustering performance, and lower power and smaller area per channel. Time-multiplexed registers are utilized in the detector for dynamic power reduction. Finally, an ultralow-voltage 8T static random access memory (SRAM) is developed to reduce area and leakage consumption when compared to D flip-flop -based memory. The proposed SSP, fabricated in 65-nm CMOS process technology, consumes only 0.175 μW/channel when processing 128 input channels at 3.2 MHz and 0.54 V, which is the lowest among the compared state-of-the-art SSPs. The proposed SSP also occupies 0.003 mm2/channel, which allows 333 channels/mm2.